Concepções de professores de ciências sobre o lúdico na prática docente - LIMA, Franciane Silva (2018)
In science teaching, students' difficulties in understanding and associating scientific content with daily reality are perceived. The need to introduce diversified teaching strategies into teaching practice arises. In this way, the playful has a relevant role in the teaching and learning process, and contributes to the holistic development of the learner by highlighting the unique characteristics of the students in a playful activity. The purpose of this study was to investigate the conceptions of the teachers who teach Science about play and its use in teaching practice in schools of higher level in the municipality of Chapadinha-MA. The research is qualitative-quantitative and semi-structured interviews were applied with teachers from six schools to obtain information about their conceptions about play and their use as teaching methodology. The analysis of the interviews was performed qualitatively, through content analysis; and quantitatively through correspondence analysis; and, content analysis using the Iramuteq software, in a qualitative-quantitative way. The following categories were constructed: Conception of teachers about the playful; The ludic in the training of science teachers; The presence of the playful in the Pedagogical Project of the schools and the presence of the ludic in the teacher's planning. Teachers have a conception of play that is not limited to games, toys and games and believe to be a methodology indispensable to their practice, although some do not use. Only seven teachers use the playful in their classes, the others justify the difficulties such as lack of pedagogical materials and science labs, indiscipline of the students, overcrowded room, absence of specific training in the area and continuing education. The results of the correspondence analysis suggest that teachers who stated that they use play in their teaching practice, generally work 40 hours, have specific training in the area and point out the presence of play in their initial and continued formation, these factors contributed significantly in presence of the ludic in the pedagogical action of these teachers of Chapadinha-MA. From this research, we can identify that all teachers recognize the importance of playful in teaching practice, however do not use for presenting an epistemological conception based on empiricism or the absence of ludic in training or didactic-pedagogical materials in school. Teaching implies a (re) construction, a reflexive practice, in which the teacher is not the target, but an element for a reconstruction. In this sense, the training process of teachers is a challenge and daily curricular practices need to be constructed and (re) constructed from the understandings and purposes attributed to playfulness